Keragaman Rhizoctonia solani Isolat Padi Varietas Ciherang, IR 64, Mekongga, dan Situ Bagendit - Manasikana, Arina; Sulandari, Sri; Priyatmojo, Achmadi (Jurnal Fitopatologi Indonesia, 2021)
Diversity of Rhizoctonia solani Isolates of Rice Varieties of Ciherang, IR 64, Mekongga, and Situ Bagendit Rice (Oryza sativa) is one of the important commodities cultivated in Indonesia. One of the important diseases on rice is sheath blight caused by Rhizoctonia solani. The research aimed to determine the effectiveness and anastomosis group of R. solani isolated from Ciherang, IR 64, Mekongga, and Situ Bagendit varieties and to know the molecular amplification of R. solani using universal primers and their genetic relationship based on the sequencing results. This research was conducted from October 2019 to July 2020 in Laboratory of Control Technology UGM. The diseased leaf samples were collected from paddy field in Pandak, Bantul. Rhizoctonia fungus was obtained by leaf tissue isolation and purified on potato dextrose agar. The R. solani isolates were classified based on cultural type, morphological characteristics, number of nuclei, anastomosis (AG) compatibility, and genetic diversity. Analysis of genetic diversity was carried out with PCR using universal primers ITS1 and ITS4. The results showed that the cultural and morphological characteristics of the isolates were various. The number of nuclei was ranged from 5 to 7 which belong to multinucleate type. The anastomosis groups (AG) compatibility test showed that the used 13 isolates are classified into C3 category (perfect anastomosis). DNA bands with results according to the target of 600-750 bp were derived from a PCR analysis. The sequencing results showed that 12 R. solani isolates showed a high genetic relationship with AG-1 IA tester isolates, except for CH 3 isolate.